Corporate Governance Mechanisms in Family Firms: Evidence from CEO Turnovers (2013)
Research Question/Issue: How sensitive is CEO turnover to firm performance in the context of family firms? Research Findings/Insights: Using a detailed database of mostly non-listed Colombian firms, we found that family ownership (direct and indirect through pyramidal structures) reduces the probability of CEO turnover when financial performance has been poor; however, we found that the opposite effect is true when families participate actively on the board of directors. These results hold true even when the manager is a family member, even though the probability of turnover is lower for a family member. This lower probability does not affect the firm's financial performance. In other words, a benevolent entrenchment of the family CEO seems to occur. Theoretical/Academic Implications: First, the theoretical premise that bad financial performance usually leads to changes in top management has been widely tested around the world; however, this study is among the few to deal with this issue in terms of closely held firm micro-data. Second, our results contribute to the growing literature on problems of agency within family firms. Third, this study contributes to the empirical literature of corporate governance in family firms for an understudied region that has gained relevance in the world economy.